Comparative study of liquefied natural gas (LNG) cold energy power generation systems in series and parallel. (15th March 2019) - Bao, Junjiang; Yuan, Tong; Zhang, Lei; Zhang, Ning; Zhang, Xiaopeng; He, Gaohong
Highlights: LNG cold energy is recovered to generate electricity. Power generation systems in series and parallel are compared. System parameters and working fluids are optimized simultaneously. Which combination method is better is discussed. The optimal combination method and working fluid are related to LNG vaporization pressure. Abstract: The irreversible loss of heat transfer between working fluid and LNG in the condensation process of the single-stage cycle which uses liquefied natural gas (LNG) cold energy to generate power is large, resulting in low power generation capacity. This can be improved effectively by combining separated cycles in series or in parallel. But which combination method (in series or in parallel) is more suitable for LNG cold energy power generation systems is not well understood. Therefore, in this paper, eight different systems are compared by combining single-stage condensation Rankine cycle and two-stage condensation Rankine cycle in series and in parallel respectively. Taking the net power output as the objective function, the key parameters and working fluids of the eight systems are simultaneously optimized at four different LNG vaporization pressures. The results show that with the increase of LNG vaporization pressure, the net power output of the system decreases. The vaporization pressure of LNG has an important influence on the system configuration (combination method) and working fluid selection. When the LNG vaporization pressure is 0.6 MPa or 2.5 MPa, the system S-T2B2 (Both top cycle and bottom cycle are two-stage condensation Rankine cycle in series) with the working fluid R32/R1150 (top cycle/bottom cycle) has the largest net power output. When the LNG vaporization pressure is 3.0 MPa or 7.0 MPa, the system P-L2R2 (Both left cycle and right cycle are two-stage condensation Rankine cycle in parallel) with the working fluid R41/R143a (left cycle/right cycle) has the highest net power output. From the economical point of view, when the LNG vaporization pressure is 0.6 MPa, the system S-T1B2 is recommended. When the LNG vaporization pressures are 2.5 MPa and 3.0 MPa, the system P-L1R1 is recommended. When the LNG vaporization pressures is 7.0 MPa, the system P-L2R2 is recommended.